Corporate Governance Dan Pengungkapan Manajemen Risiko Bank Syariah Di Indonesia - Annisa Difa Saufanny; Siti Khomsatun (Jurnal Akuntansi dan Keuangan Islam, 2017)
Based on Peraturan Bank Indonesia Nomor 13/23/PBI/2011, Indonesian Islamic bank has faced Rate of Return Risk and Equity Investment Risk that has been not faced by conventional bank. Moreover, Islamic bank also has had more reputation risk and compliance risk than conventional bank. The objective of this research is to provide empirical evidence of the influence of corporate governance on the risk management disclosure for Indonesian Islamic banking. Good Corporate Governance is proxied by total of Commissioners Board, total of  Independent Commissioners Board, total of Audit Committee, total of  Independent Audit Committee, and Sharia Supervisory Board. The method used in this research is multiple linear regression panel data. Using 35 unbalanced panel data from 11 Indonesia Islamic Bank for 2012 -2015,  the result shows that only total audit committees that influence the risk management disclosures of Indonesian Islamic Bank